Assessing the Impact of Artificial Intelligence on Productivity and Global Market Competitiveness: A Case Study of Nigeria - Vaikosen, Bridget; Magini, Gideon Ufuomanefe (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
The emergence of Artificial Intelligence (AI) has transformed the global economic terrain, generating intense debate about its implications on productivity, business models, and employment among scholars. Nigeria, Africa’s largest economy, is faced with the challenges of improving productivity and competitiveness in global markets. The adoption of AI technologies serves as a panacea and offers potential solutions to these challenges if effectively utilised. This study investigates the impact of AI on productivity and global market competitiveness in Nigeria, covering the period 1999-2023. The study employs a two-pronged approach to data analysis, combining descriptive statistics and regression analysis. (Pooled Least Squares) techniques. Variables used are: Productivity (output) dependent variable, while independent variables are: AI adoption (AI investment), capital stock, labour force, human capital (education and training) and global market competitiveness (foreign direct investment). The results from the study reveal that the model as a whole is statistically significant, indicating the independent variables collectively have a strong influence on the dependent variable. The result further reveals that AI investments and the Labour force have a positive and significant impact on productivity in Nigeria’s global competitiveness. Capital stock has a positive but insignificant impact on productivity and global market competitiveness, while education and training and Foreign direct investment have a negative and insignificant impact on productivity and competitiveness The study amongst others therefore recommends that Nigeria government should develop a national AI strategy, by investing in AI infrastructure:, such as data centers and high- speed internet, that can support the growth of AI- driven businesses, effective and efficient education and training should be done and carried out by the government through programs such as skills acquisition, vocational training, training and re-training and to efficiently utilized foreign direct investment to enhance productivity.